Heart failure hospitalizations in persons with and without diabetes in an Italian region: 2008-2018. (30th September 2020) - Scampoli, P; Di Giovanni, P; Cedrone, F; D'Addezio, M; Di Martino, G; Masciarelli, M; Meo, F; Staniscia, T
Abstract: Background: Hospitalization rate for heart failure (HF) is considered a prevention quality indicator and it is used as a tool to evaluate health services quality. This study aims to assess time trends in HF hospitalizations in a region of Southern Italy, focusing on diabetes mellitus as comorbidity. Methods: Data were collected from hospital discharge records. All patients aged 18 or over hospitalized for HF in Abruzzo between 2008 and 2018 were selected, either with or without a diagnostic code of diabetes. Admissions for cardiac procedures were excluded. For each year, gender- and age-adjusted standardized hospitalization rates were calculated. Predictors of HF admissions were estimated by a multivariable regression model. Results: Over the study period, 60, 737 HF admissions occurred, 34, 518 of which among people aged more than 65 (56.8%). A total of 15, 424 hospitalizations were performed among diabetic patients (25.4%). The overall age- and gender-adjusted HF hospitalization rate declined substantially from 2008 to 2018 (-12.1%). Diabetes (adjOR 2.48; 95%CI 2.41-2.55), myocardial infarction (adjOR 3.92; 95%CI 3.70-4.14), peripheral vascular disease (adjOR 2.30; 95%CI 2.16-2.44), chronic obstructive pulmonary disease (adjOR 3.97; 95%CI 3.86-4.09) and renal disease (adjOR 5.61; 95%CI 5.44-5.78) were factors associated to an increased risk of HF hospitalization. Although HF admission rates remained higher, a significant reduction was highlighted among diabetic patients (-34.7%). Instead, time trend was nearly stable among persons without diabetes (+2.7%). Conclusions: This study has shown a decline in HF hospitalization rate over the period considered, particularly among diabetic patients. HF hospitalization may be potentially avoided with good outpatient care. As the causes for HF admissions may include poor quality of care or problems accessing care, it is worthwhile to identify the triggering factors and the potential targets for an early intervention. Key messages: A reduction of HF admissions was observed only among diabetics and not among people without diabetes. As the HF hospitalizations are potentially preventable, the knowledge of the epidemiology is crucial for management of preventive health care.